Impact of Environmental Factors on Breakdown Characteristics of Air Insulation in Power Distribution Components of Electrical Aircraft - Koseoglu, Ali (My University, 2025)
Abstract Growing concerns on environmental issues challenge scientists and engineers to create greener technologies on a vast area of industrial and commercial applications. Aviation, as one of the major human activities responsible for the environmental impacts, is among the most trending topics in this effort for transition to more eco-friendly technologies. While electrical aircraft have been experimented from as early as 1885, achieved by Gaston Tissandier by flying a small airship powered by an electric motor, the scale of aircraft needed today is significantly larger. The more powerful electrical powertrains needed to achieve this goal call for higher levels of system voltage to reduce the weight and enable competitive designs. Although well-studied for land and sea applications, the use of high voltage systems is a relatively new area for aviation systems. A growing demand for research and development is emerging for creating regulations, technical standards, testing methods and know-how for applying high voltage solutions in electrical aircraft. This thesis explored the implications of implementing high voltage direct current systems to be used in hybrid or all-electric electrical aircraft with a focus on the performance of the dielectric systems under expected ambient conditions in high altitudes, namely extreme ambient temperatures (TA), low air pressure (p) and various relative humidity (RH) levels. To achieve the goal, experimental setups of vacuum and climate conditioning chambers were utilized to create ambient conditions an electrical aircraft may experience, and respective breakdown voltage for the insulation system for various scenarios were measured. It was observed that lower air pressure and relative humidity levels create unfavorable conditions for the insulation system, while lower ambient temperature increases the breakdown voltage. The combined effect of higher altitude conditions was evaluated to be of performance depreciative nature for the insulation systems as the altitude increases up to 25,000 feet. It was also concluded that significantly lower insulation performance may emerge around the dew point of water in the air.
Keywords: Keywords: High Voltage Direct Current, Electric Aircraft, Insulation Systems, Townsend Mechanism, Paschen’s Law, Non-Uniform Electrical Fields, Breakdown Test, Vacuum Chamber, Climate Chamber.